(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: PNS (primary idiopathic nephrotic syndrome) is a frequent renal nephropathy that manifests as severe proteinuria and hypoalbuminemia. Some individuals have poor reactions and clinical results when treated with conventional medicine. Despite significant advancements in its treatment, there are still ongoing searches to seek treatment. Curcuma xanthorrhixa Roxb. (temulawak) and Nigella sativa (black cumin) rhizome contain many biological properties, including potent antioxidant and renoprotective effects. Aim: This study sought to determine whether the combination of Nigella sativa and Curcuma xanthorrhiza Roxb. reduces hyperlipidemia in Nephrotic syndrome. Methods: This was an experimental study with a posttest-only control group design involving 24 male Wistar rats divided into three groups; the negative control group received no treatment, the positive control group received an adriamycin (ADR) 6,5 mg/kg BW injection, and the intervention group received rhizome extract temulawak (1000 mg/kg BW) and black cumin (250 mg/kg BW). The serum levels of total cholesterol, triglycerides, LDL cholesterol, and HDL cholesterol are examined post-treatment. Results: The combination of Nigella sativa extract and Curcuma xanthorrhiza rhizome reduced total cholesterol (p=0.006) and triglyceride (p=0.003). There was no significant result observed for HDL(p=0.432) and LDL-c (p=0.317) (Kruskal-Wallis test; p <0.05). Conclusion: Temulawak and black cumin extracts can reduce total cholesterol and triglyceride. However, no significant result was observed in NS model rats in HDL and LDL levels.